2022
DOI: 10.3389/fphys.2022.906302
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Prone Positioning With Individualized Positive End-Expiratory Pressure in Acute Respiratory Distress Syndrome Using Electrical Impedance Tomography

Abstract: Background: Positive end-expiratory pressure (PEEP) optimization during prone positioning remains under debate in acute respiratory distress syndrome (ARDS). This study aimed to investigate the effect of prone position on the optimal PEEP guided by electrical impedance tomography (EIT).Methods: We conducted a retrospective analysis on nineteen ARDS patients in a single intensive care unit. All patients underwent PEEP titration guided by EIT in both supine and prone positions. EIT-derived parameters, including … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…(1) Since all healthy volunteers were male, the gender could cause the selection bias. (2) Since the lung image of diaphragm-based EIT-belt plane could be improved in the disagree group, other EIT-related parameters such as global inhomogeneity index, center of ventilation, regional ventilation delay and pendelluft parameters might be impacted [ 4 , 18 ]. Further study is required to validate the impact degree of diaphragm-based EIT-belt other EIT-related parameters.…”
Section: Discussionmentioning
confidence: 99%
“…(1) Since all healthy volunteers were male, the gender could cause the selection bias. (2) Since the lung image of diaphragm-based EIT-belt plane could be improved in the disagree group, other EIT-related parameters such as global inhomogeneity index, center of ventilation, regional ventilation delay and pendelluft parameters might be impacted [ 4 , 18 ]. Further study is required to validate the impact degree of diaphragm-based EIT-belt other EIT-related parameters.…”
Section: Discussionmentioning
confidence: 99%
“…A study in ARDS patients with individualized PEEP setting by EIT found smaller RVD values and more dorsal ventilation with higher CoV in prone compared to supine position in patients with higher body mass index [42]. A retrospective analysis of EIT data acquired during a decremental PEEP trial in obese and nonobese patients showed that PEEP derived from RVD was lower than when GI or a balanced ventral and dorsal fraction of ventilation were used to identify the optimum PEEP [43].…”
Section: Detection Of Temporal Distribution Of Ventilation and Its Us...mentioning
confidence: 99%